Synergetic water purification modulus for the methylene degradation in the water-methylene mixtures - Nadareishvili, M.; Gegechkori, T.; Mamniashvili, G.; Zedginidze, T.; Petriashvili, T. (Edelweiss Applied Science and Technology, 2025)
A simple and compact module has been designed and tested for the implementation of a synergetic process of water purification using the example of methylene impurity in a methylene-water mixture under the simultaneous action of ozonation, ultraviolet radiation, ultrasound, and nanomaterials based on the TiO2 photocatalyst. It has been shown that adding TiO2 nanopowder to the mixture dramatically accelerates the process of methylene degradation, with the simultaneous action of the other three factors of the synergetic process. Internal surfaces of iron modulus were covered using electroless technology by Ni-TiO2 layer, which proved to be a good photocatalyst and having good cohesion and abrasion resisting properties. By selecting the composition of the used photocatalyst and combining different water purification mechanisms, it is possible to obtain an environmentally friendly technology to purify drinking and technical water. The use of modulus ensures the continuity of the water disinfection procedure since cleaning of the elements located in the chamber from various types of dirt is completed during the operation of the device and does not require interruption of the technological process. The outlet removes the dirt and other particles from the sterilization chamber.